-5x+7=-4(2x+5)

Simple and best practice solution for -5x+7=-4(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+7=-4(2x+5) equation:


Simplifying
-5x + 7 = -4(2x + 5)
Reorder the terms:
7 + -5x = -4(2x + 5)
Reorder the terms:
7 + -5x = -4(5 + 2x)
7 + -5x = (5 * -4 + 2x * -4)
7 + -5x = (-20 + -8x)
Solving
7 + -5x = -20 + -8x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8x' to each side of the equation.
7 + -5x + 8x = -20 + -8x + 8x
Combine like terms: -5x + 8x = 3x
7 + 3x = -20 + -8x + 8x
Combine like terms: -8x + 8x = 0
7 + 3x = -20 + 0
7 + 3x = -20
Add '-7' to each side of the equation.
7 + -7 + 3x = -20 + -7
Combine like terms: 7 + -7 = 0
0 + 3x = -20 + -7
3x = -20 + -7
Combine like terms: -20 + -7 = -27
3x = -27
Divide each side by '3'.
x = -9
Simplifying
x = -9

You can always share this solution

See similar equations:

| -18r+3r=4r+56 | | 1-7x=3x-9 | | 17+4x=7x+8 | | 2x=4+x+2 | | x=sin(79) | | =sin(79) | | 6(w-7)-3w=-39 | | 9+4=8(5+K) | | 12=-8x+2(x+3) | | 5*1=9 | | 7(v-5)+3u=5 | | 4(2x-3)=5(x+5) | | 2z^2-21z-336=0 | | 29=7(u+3)-5u | | -22=5(y-8)-2y | | 2a+9=4a+3 | | 4t+16=2t+36 | | x^17/4x^9 | | 3t+15=39 | | Y=3x(x-8) | | f(4)=8 | | f(x)=2x^3+11x^2+17x+6 | | 4-6t=2t-12 | | (7/10a^2b)-(3/14ab^3) | | 6x-15x-19=91 | | (7/10a2b)-(3/14ab3) | | 4x-3(2-7x)=3x+9 | | (k+1)(k-1)=-72 | | 2+y=71 | | Lnx=5.67 | | 3xy+4x^2=90 | | 18y/45 | | 2(h+5)-5(1-2h)=7-4(3-h) | | 5(3x-8)-7=-2(4x+5)+10 | | 5(3x-8)=-2(4x+5)+10 | | -6(y+2)+5(y+3)=16 | | -4x+4x^2+1=0 | | -10(s+1)=36 | | 4(f-5)=-48 | | 3(a-1)=27 | | 3a-1=27 | | 0.5(X-6)=9 | | 4c-(7-c)=-17 | | 19w=1.33 | | 3x^2+3y^2+6x-6y-3=0 | | c/5-6=4;10 | | 3t-8=3 | | 2a+b=8.4 | | 185=19x | | 1380=x^2*(0.04x+55) | | 5(2x+8)=16 | | 3(8x-2)=119 | | 1=3-4x+2+5x+4(3-x) | | 1=3-4x+12+5x+4(3-x) | | 15x+(5-6x)-2-(-x+3)=(7x+23)-x+(3-2x) | | x^3=96x-256 | | 1=-4x-4x | | D/6-12=-2 | | y-10=0+x | | 3.61n=8+2.135n | | 6x=48-10x | | 0=-x^2+9x+10 | | x^2(0.06x+51)=1382 | | x^2-3x+7=2x-3 | | .8333x-14=-4 |


Related pages


4w solutions4y 2x 150solve sin2x cos2xsquare root of 9615x-7 2-4xx 4y 20sin 3x derivativecos 2x derivativefactor tree for 964x4 solvederive ln 2xwhats gcflog5 25 xvariable calculator with fractionsprime factorization 32gcf calculaterderivative x ln xgraph the equation 3x-2y 6is 567 a prime number190-51ln 5xgcf and lcm of 36 and 452x-4y 4solve logx 5 36 24x-5y 0prime factorization of 128prime factorization of 132what are the factors of 6x 66x 3y 4tan 4x-sec 4x4y 2x 1504x 2y 8 0factorise 2x 4prime factorization 85factor 3x 2 5x 2what is the prime factorization of 735prime factorization of 162least common denominator calculatorroman numerals 1986pe mgh9pi96-3007x 5 5xprime factorization of 1701234567890 0987654321the prime factorization of 175prime factorization 7279 in roman numerals3x 5y 1derivative of tan 3x3x derivative40x2800lcm of four numberscalculator dividing fractionswhat is the prime factorization of 142simplify the square root of 98equations solver with stepsderivative e 4x1001 roman numeralsconvert percentage to decimal calculator55yprime factorization of 91gcf of 54 and 63what is the prime factorization of 70gcf of two monomials calculatorfactorization calculatorderivative of sin 4x1.4f1 0.9999999992x graphmultiplication of fraction calculatorone step equation calculatorlnx1tan 2 x derivativex3 y3simplify 625derivative of e lnxprime factorization of 1900540-170